POTENSI PENGGUNAAN LIMBAH KELAPA SAWIT SEBAGAI AGREGAT PENGISI PADA CAMPURAN HOT ROLLED SHEET-BASE - Suparma, Latif Budi; Panggabean, Tunggul W.; Mude, Sandra (Jurnal Transportasi, 2014)
The development of the oil industry in Indonesia, have an impact on the increase in solid waste generated from the processing of fresh fruit bunches, which can be either fruit fibers and shells. Based on several studies and physical form of ash fiber palm (palm oil fiber ash) and ash shell palm (palm oil shell ash), it is seen have similarities with fly ash which has been widely used as a filler for asphalt mixtures. In this research, further study would be performed whether any potential of oil palm ash to be used in the mix for road pavement, especially in HRS-Base mixture. The study was conducted by varying the oil palm ash as a filler replacement of 0% , 25%, 50%, 75%, and 100%. Furthermore mixture design of each variation was based on the Marshall method. Test characteristics of the mixture are then performed after obtaining the optimum asphalt content by testing the remaining strength based on the Marshall test and indirect tensile test. Results of laboratory design by Marshall method of the HRS - Base utilizing aggregate filler ash palm fiber and ash oil palm shell, it is generally found that the greater the ash content of the oil palm (fiber and shell) resulting in greater the asphalt needed. Test results indicate that there is any possibility of utilizing ash palm oil in HRS-Base mixture. The results also indicated that the HRS-Base mixture utilizing fine filler of ash palm fiber and ash oil palm shell potentially resistant to deformation, however less resistant to cracking due to tensile. Keywords: palm oil fiber ash, palm oil shell ash, filler replacement, HRS-Base Perkembangan industri sawit di Indonesia, berdampak pada peningkatan limbah padat yang dihasilkan dari pengolahan tandan buah segar (TBS), yang dapat berupa serabut buah dan cangkang. Berdasarkan beberapa penelitian dan bentuk fisik abu serat kelapa sawit (palm oil fibre ash) dan abu cangkang kelapa sawit (palm oil shell ash), terlihat adanya persamaan dengan fly ash yang telah banyak digunakan sebagai filler untuk campuran beraspal. Pada penelitian ini diteliti potensi abu kelapa sawit untuk digunakan dalam campuran untuk perkerasan jalan, khususnya campuran HRS-Base. Penelitian dilakukan dengan membuat variasi abu kelapa sawit sebagai pengganti filler0%, 25%, 50%, 75%, dan 100%. Selanjutnya dirancang campuran pada masing-masing variasi dengan Metode Marshall. Uji karakteristik campuran kemudian dilakukan setelah diperoleh campuran rancangan dengan menguji kekuatan sisa berdasarkan uji Marshall dan uji tarik tak langsung. Hasil perancangan laboratorium dengan metode Marshall untuk campuran HRS-Base dengan menggunakan agregat pengisi abu serat kelapa sawit dan abu cangkang kelapa sawit secara umum menunjukkan semakin besar kandungan abu kelapa sawit semakin besar kebutuhan akan aspal. Hasil uji karakteristik campuran menunjukkan bahwa campuran HRS-Base menggunakan agregat pengisi abu serat kelapa sawit dan abu cangkang kelapa sawit berpotensi tahan terhadap deformasi namun kurang tahan terhadap retak karena tarik. Kata-kata kunci: abu serat kelapa sawit, abu cangkang kelapa sawit, pengganti agregat pengisi, HRS-Base